Analisis Kepuasan Pengguna Canva Dan Slidego Dikalangan Mahasiswa Menggunakan Metode Costumer Satisfaction Index (CSI) - melzan sabri sabri; RG. Guntur Alam; Gunawan (JSAI (Journal Scientific and Applied Informatics), 2025)
Canva and slidego are graphic design platforms that are widely used by students. This study uses the Customer Satisfaction Index (CSI) method to measure and understand how satisfied students are with the Canva and Slidego presentation design platforms. This is based on the fact that these platforms are the main choice for students to create attractive professional presentations. This study uses a quantitative, descriptive method by collecting data from students who use both applications through an online questionnaire. To measure overall user satisfaction, but there are also important attributes that affect user satisfaction. such as ease of use, completeness of features. The results of the calculations carried out using the (CSI) method show a value of the percentage of user satisfaction of 85.4115773 Based on the CSI scale, the results are categorized as "very satisfied" with the Canva application. While the Slidego application gets a value of 80.920309% categorized as "Satisfied", so in the results of this CSI calculation, the Canva application has a value greater than the Slidego application value, so the conclusion is that the Canva application is more and more often used by users.